Information Technology Services Audit Lembaga Perkreditan Desa Using COBIT 5 Framework - I Nyoman Angga Prabawa; Dewa Agung Krishna Arimbawa; Putu Arya Mertasana (International Journal of Engineering and Emerging Technology, 2018)
Lembaga Perkreditan Desa or LPD is an institution that is present to assist and collect community finances in a village and is managed independently by desa pakraman in Bali Province. One LPD in Bali, LPD Desa Pakraman Gelgel has a very vital role in Gelgel Village and its surroundings because of its business activities that effectively help rural communities in capital assistance, deposit and credit services, and other financial services. In its development, the LPD of Desa Pakraman Gelgel has been growing rapidly and utilizing information technology services as a support for business management. The critical point of finding in IT service audits related is a problem that needs to be evaluated. Using COBIT 5 framework, the level of importance analyzed was obtained by three process domains BAI09, MEA03, and EDM03. The results showed that the level of capability of MEA03 and EDM03 reached level 4 which had met LPD expectations, but BAI09 reached level 2 which required recommendations to reach the target value of the gap. Recommendations are given to assist stakeholders or managerial in improving the achievement of the gap from the BAI09 domain regarding the management of IT service assets